A Work study on NICFUR Furniture - Cariño, Don Mikhail (College of Engineering, 1996)
The application of Work Study and Systems & Procedures is the scope of the study being conducted on the plant site, Nicfur Furnitures. The scope of the study being conducted is limited to only one furniture, the Visitor's Chair, for reasons that is passes through all the four department of the plant (Milling, Assembly, Finishing & Upholstery). The limitation of the study is that it is to be studied only in one semester (3 months). The first part of the study deals with the two areas of Work Study, namely Methods Study and Work Measurement. In Methods Study, the documentation of the whole system was studied following the flow of the chosen furniture and other pertinent information. The appropriate charts and diagrams were used for the documentation process like the Flow Process Chart, Flow diagrams and Layouts. The findings about the company were also examined, then given the appropriate recommendations. Secondly, the application of Work Measurement was conducted, mainly in the Finishing dept.due to time constraints, were all the relevant data about the rate of work of the workers were timed, rated and analyzed in order to come up with the standard time of production by the use of the Direct Time Study Method. The second part of the study deals with the concept of Systems and Procedures. This included the study of the various forms being used in the company, and also the creation of the S&P Manual which gives a more detailed explanation of the recommendations, as well as their corresponding methods of installation and maintenance in order to increase efficiency and improve work. A Cost and Benefit analysis of each recommendation was also included. In the complete and final analysis of the systems in Nicfur, the majority of recommended changes revolve around the major problem analyzed as dominant in the company, Poor Work Area.